Recent synthetic methodologies for imidazo[1, 5-a]pyridines and related heterocycles. Issue 17 (8th April 2022) - Ramana Reddy, Mittapalli; Darapaneni, Chandra Mohan; Patil, Rajendra D.; Kumari, Harshita
Abstract : This review summarizes the recent developments in the construction of imidazo[1, 5- a ]pyridines using cyclocondensation, cycloaddition, oxidative cyclization, and transannulation reactions. Abstract : Imidazo[1, 5- a ]pyridine is a significant structural component of a large number of agrochemicals and pharmaceuticals. The synthesis of imidazo[1, 5- a ]pyridine has been a subject of intense research for numerous decades. A large number of transformations are now available to conveniently access imidazo[1, 5- a ]pyridine from readily available starting materials. This review details the recent development in imidazo[1, 5- a ]pyridine construction involving cyclocondensation, cycloaddition, oxidative cyclization, and transannulation reactions.